Which one is the most accurate naming convention: cutaneous lipofibroma or pedunculated lipofibroma? (Dermatology Reports, 2023)
This is a case of a large pedunculated lipofibroma on the left axilla in a 36-year-old woman. The lesion was excised completely with no recurrence after one year of follow-up. A new name for this rare entity is proposed to be more inclusive of all lesions of pedunculated lipofibroma and to differentiate it from another entity called fibrolipoma.